Milk proteins - Rodrigues, Célia Fortuna (2015)
Milk contains many types of proteins which are classified in two general categories caseins and whey proteins. Due to their nutritional and functional properties milk proteins products are widely used in the food industry. This chapter summarizes the current knowledge on milk protein fraction and their biological properties. The production of the mains protein-enriched products is described. In addition an overview of the current and potential biomedical applications of milk proteins is given.